Implementasi Model Kesuksesan Sistem Informasi DeLone dan McLean pada SVOD Platform (Studi Kasus: Netflix) - Nico Yonatan Wicaksana; Jarot Sembodo Suroso (ITEJ (Information Technology Engineering Journals), 2022)
Abstract — Netflix is a pioneer in the video on demand subscription platform in Indonesia and remains the most popular video streaming service in the world, but Netflix has been forced to relinquish its position as the SVOD provider with the highest subscribers to become the fourth position in Indonesia. The SI DeLone and McLean success model modified by Hudin and Riana in 2016 is used in this study to determine Netflix's success factors and can be used for sustainability progress. The Smart PLS software program was used to evaluate survey data from 410 respondents, which indicated that information quality had a significant effect on system usage (Statistics T=2.85; P-Values=0.005; F-Square=0.023) and user satisfaction ( Statistics T=2.927; P-Values=0.004; F-Square=0.024). However, the quality of the system has no significant effect on system use (T-Statistics=2.628; P-Values=0.009; F-Square=0.018) but has a significant effect on user satisfaction (T-Statistics=5.219; P-Values =0.000; F-Square = 0.086). In addition, service quality has a significant effect on system usage (T-Statistics=3.447; P-Values=0.001; F-Square=0.032) and user satisfaction (T-Statistics=3.654; P-Values=0.000; F-Square = 0.043 ). The use of the system also has a significant effect on net benefits (Statistics T=6.625; P-Values=0.000; F-Square=0.16) and user satisfaction (Statistics-T=7.417; P-Value=0.000; F-Square= 0, 14). The last factor is user satisfaction which has a significant effect on net profit (T-Statistics=6.509; P-Values=0.000; F-Square=0.124). Suggestions for further research are to develop a model with other models to achieve better research results and to find out more independent variables that influence the success rate of the Netflix platform in Indonesia.